Scripture and Moral Examples in Pietism and Kant's Religion - Head, Jonathan (2018)
This paper argues for considerable Pietist influence upon Kant's Religion within the Bounds of Mere Reason, through a focus upon the topics of Scripture and the use of moral examples within the context of a religious community. The recommended approaches to the use of Scripture in both Religion and the Pietist theology of Spener are compared, revealing deep parallels between Kant and core Pietist thought. In addition, the importance of moral examples in cultivating true, 'moral faith' is examined in both Kant and Pietism as a further major point of influence. The paper concludes by noting the potential significance of this Pietist influence for our wider understanding of Kant's thought in the Critical period.
Keywords: Kant; Pietism; Spener; moral archetype; moral examples; Scripture